Proyecto de factibilidad para la creación de una empresa productora y comercializadora de helados de Curuba en la ciudad de Loja - Añazco Rojas, Juan Carlos (2016)
The present investigation developed in Loja's city, Loja's Province, having as principal aim determine the feasibility for the creation of a producing company and comercializadora of ice creams of curuba in Loja's city. With this purpose there was realized the study based on such different methods as deductively, inductively, analytical, synthetically, statistically and the utilization of diverse technologies of investigation as the direct observation and the application of surveys to a sample of 399 potential clients in the city of Loja and 53 offerers of existing ice creams in the locality. By means of the accomplishment of the Market Research one determined that the market puts it is shaped by the inhabitants of Loja's city, provided that his low price allows that the majority should have the economic aptitude to buy the product that is going to offer. Tabulated the surveys have been analyzed and there have been inferred the results that allowed to establish that the effective demand is 10.320.040 units of ice cream, the offer is 1.721.705 units, turning out to be an unsatisfied demand of 8.598.335 units of ice cream on the basis of curuba. By means of the Technical Study it was possible to establish an installed capacity of 113.120 units of ice cream, which means 1,32 % of the unsatisfied demand; while the used capacity is 119.808 ice creams, which it represents 90 % of the total of the facilities of the company; for second years it increases in 5 % and from the third year one works with 99 %. In addition, it was achieved to identify the ideal location of the project concluding that it will be located in Loja's city, specifically Manuel Carrión Pinzano Occidental Avenue and Vicente Paz, since it is the suitable place for the execution of the activities. To start the project he needs of 6 employees, between administrative officers and operatively, helping to diminish partly the rate of unemployment in the sector. The company will be constituted legally as Company of Limited Responsibility, shaped by four shareholders. The project needs of an investment in fixed assets of $ 17.961,30, in intangible assets of $ 1.821,75 and in the capital of work of $ 5.202,52 dollars, which totalizes an initial investment of $ 24.985,57 dollars; of this total 59,98% that corresponds to $ 14.985,57 will be contributed by the shareholders and 40,02% remaining will be financed by means of a credit in the Bank of the Pichincha, with an amount of 10.000 dollars. By means of the picture of total costs it was possible to establish that the total cost for the first year is of $ 65.100,52 and the income is of $ 87.885,70, which fragmenting in fixed and variable costs allowed to establish the point of balance for the first year in 53,35% of utilization of the installed capacity and in the obtaining $ 46.885,94 of income for sales. Additional it was possible to establish, across the State of Results that the present project were achieving usefulness for the first year of $ 13.595,92; of equal form the flows were calculated for ten years of useful life, being for the first year of 17.735,24 dollars and for other years they are all positives. The realized Cash flow allowed to elaborate the Financial Evaluation, which financial indicators are: Current Clear Value 72.486,64 (VAN) of $; Internal Rate of Return (TIR) reaches 73,97%, Relation I Benefit Cost (B/C) of 1,33; Period of Capital recovery (PRC) of 1 year, 4 months and 21 days; finally, the Analysis of Sensibility demonstrates that the project supports an increase in the Costs of 18,75 % and to a decrease in the Income of 14,00 %. Taking the favorable results as a base in all the stages that shape the study of feasibility, one concludes that start the company will generate important economic benefits to his investors as to the collectivity where it will be located, therefore his execution is feasible.